Leucocoprinus rhodolepis (Agaricaceae: Basidiomycota), a new species from Brazilian semi-arid region - Nathália U. Ferretti-Cisneros; Alexandre G. S. Silva-Filho; Felipe Wartchow (Revista Mexicana de Biodiversidad)
A novel Leucocoprinus species was collected from the semi-arid region of Brazil in the Caatinga domain. Leucocoprinus rhodolepis is described based on morphological data. It is well characterized by its white pileus with distinct orange-pink pileal squamules at the center, ellipsoid basidiospores measuring 6.9-7.8 × 4.9-5.9 μm lacking an apical germ pore, and clavate to broadly clavate rarely ventricose-capitate cheilocystidia. Detailed macro- and micro-morphological descriptions and illustrations are provided, as well as a comparison with related species and a brief discussion about its conservation status.